2016
DOI: 10.1037/abn0000157
|View full text |Cite
|
Sign up to set email alerts
|

Visual integration dysfunction in schizophrenia arises by the first psychotic episode and worsens with illness duration.

Abstract: Visual integration dysfunction characterizes schizophrenia, but prior studies have not yet established whether the problem arises by the first psychotic episode or worsens with illness duration. To investigate the issue, we compared chronic schizophrenia patients (SZs), first episode psychosis patients (FEs), and well-matched healthy controls on a brief but sensitive psychophysical task in which subjects attempted to locate an integrated shape embedded in noise. Task difficulty depended on the number of noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 24 publications
3
33
0
1
Order By: Relevance
“…For example, temporary or situation-dependent factors that add perceptual noise (e.g., due to distance or lighting intensity [17]) can reduce the precision of gaze perception, and those that evoke a self-related belief (e.g., when one's name is being called [18]) can increase the likelihood of perceiving selfdirected gaze. Additionally, in psychiatric disorders in which abnormal gaze perception is well-documented (e.g., schizophrenia, ASD, and social anxiety), a large body of evidence also suggests disruptions in either/both visual perception and/or self-referential processing (e.g., dysfunction in low-level visual processing in ASD [19]; dysregulated self-referential tendencies in social anxiety [20,21]; deficits in both low-level visual processing [22,23] and higher-level self-referential processes [24] in schizophrenia). Therefore, dissociating these two cognitive processes can help us identify the sources of deficits underlying abnormal gaze perception in different psychiatric disorders as well as understand individual differences across the healthpsychopathology continuum.…”
Section: Introductionmentioning
confidence: 99%
“…For example, temporary or situation-dependent factors that add perceptual noise (e.g., due to distance or lighting intensity [17]) can reduce the precision of gaze perception, and those that evoke a self-related belief (e.g., when one's name is being called [18]) can increase the likelihood of perceiving selfdirected gaze. Additionally, in psychiatric disorders in which abnormal gaze perception is well-documented (e.g., schizophrenia, ASD, and social anxiety), a large body of evidence also suggests disruptions in either/both visual perception and/or self-referential processing (e.g., dysfunction in low-level visual processing in ASD [19]; dysregulated self-referential tendencies in social anxiety [20,21]; deficits in both low-level visual processing [22,23] and higher-level self-referential processes [24] in schizophrenia). Therefore, dissociating these two cognitive processes can help us identify the sources of deficits underlying abnormal gaze perception in different psychiatric disorders as well as understand individual differences across the healthpsychopathology continuum.…”
Section: Introductionmentioning
confidence: 99%
“…Over 60 laboratory studies have demonstrated reduced perceptual organization in schizophrenia [9][10][11] . These abnormalities arise by the first psychotic episode and become more pronounced with increasing chronicity [11] .…”
Section: Perceptual Fragmentationmentioning
confidence: 99%
“…These abnormalities arise by the first psychotic episode and become more pronounced with increasing chronicity [11] . They have not been found in other psychiatric disorders 1 [12][13][14][15][16] , and, among people with schizophrenia, they are associated with histories of poor premorbid functioning, disorganized symptoms, and poorer treatment response, suggesting they are an aspect of a more severely ill patient subtype [17] .…”
Section: Perceptual Fragmentationmentioning
confidence: 99%
“…Threshold performance on this task reflects the amount of orientation noise that can be tolerated when making these judgments. Although this task has received strong research interest, and consistently revealed poorer performance in schizophrenia patients [e.g., ( 14 17 )], as early as the first psychotic episode ( 18 ), much less is known about these particular integration abilities in healthy individuals with high levels of schizotypy, who are at increased risk for schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Building on prior research, we chose to focus on positive schizotypy, comparing visual integration abilities in healthy individuals with high and low scores on the Perceptual Aberrations (PAb) scale ( 36 ). Based on previous evidence [e.g., ( 14 , 18 , 21 , 22 )] we predicted that, compared to the Low PAb group, the High PAb group would exhibit poorer tolerance to local noise (lower thresholds and lower proportion of correct responses on the RFJOT task) and reduced global integration efficiency (shallower slope values on the RFIT). In addition, in order to address the issue of specificity, the influence of other positive, disorganization and negative schizotypy traits was also explored.…”
Section: Introductionmentioning
confidence: 99%